3D Printing: Conformal Geometry and Multimaterial Additive Manufacturing through Freeform Transformation of Building Layers (Adv. Mater. 11/2021). Issue 11 (16th March 2021) - Huang, Jigang; Ware, Henry Oliver T.; Hai, Rihan; Shao, Guangbin; Sun, Cheng
Abstract : In article number 2005672, Cheng Sun and co‐workers report a new additive manufacturing process that unleashes the full six degrees‐of‐freedom in transforming and assembling each of the building layers into the final geometry. It not only enables discrete conformal transformation, allowing 3D‐printed biomedical implants to be customized for specific patient anatomy, but more importantly, also establishes multimaterial, multi‐axis 3D‐printing capability for integrating functional modules made of dissimilar materials in 3D‐printed devices.